2006
DOI: 10.1295/polymj.pj2006013
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Contributions to Chain Stiffness and Excluded-Volume Effects in Sodium Poly(2-acrylamido-2-methylpropanesulfonate) Solutions

Abstract: ABSTRACT:Chain stiffness and excluded-volume effects in 0.005-1 M aqueous NaCl solutions of sodium poly(2-acrylamido-2-methylpropanesulfonate) (Na PAMPS) at 25 C have been studied by viscometry on 15 samples with weight-average molecular weights of 1:7 Â 10 3 -7:1 Â 10 5 . The molecular weight dependence of intrinsic viscosity at each NaCl concentration C s is analyzed by a combination of Yoshizaki et al.'s theory for unperturbed wormlike chains and the quasi-two-parameter theory for excluded-volume effects to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…This indicates that no phase separation takes place in their AP−MP mixture solutions. Yusa et al's 5 AP and MP samples have longer P block chains, so that the solubility of their AP and MP with the Avogadro constant N A , the classical electron radius a e (= 2.82 × 10 −13 cm), and the average contrast factor γ av (calculated from the measured or literature value 28 of the partial specific volume; see eq S4). At C S = 2 M, the profile shows essentially no angular dependence at k < 0.2 nm −1 , indicating that no large self-assemblies are formed in the mixture solution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that no phase separation takes place in their AP−MP mixture solutions. Yusa et al's 5 AP and MP samples have longer P block chains, so that the solubility of their AP and MP with the Avogadro constant N A , the classical electron radius a e (= 2.82 × 10 −13 cm), and the average contrast factor γ av (calculated from the measured or literature value 28 of the partial specific volume; see eq S4). At C S = 2 M, the profile shows essentially no angular dependence at k < 0.2 nm −1 , indicating that no large self-assemblies are formed in the mixture solution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Figure compares SAXS profiles for aqueous solutions of the AP–MP mixture ( x + = 0.6) with c = 0.005 g/cm 3 at different NaCl molar concentrations C S . In the ordinate, K e is the optical constant defined by with the Avogadro constant N A , the classical electron radius a e (= 2.82 × 10 –13 cm), and the average contrast factor γ av (calculated from the measured or literature value of the partial specific volume; see eq S4). At C S = 2 M, the profile shows essentially no angular dependence at k < 0.2 nm –1 , indicating that no large self-assemblies are formed in the mixture solution.…”
Section: Resultsmentioning
confidence: 99%
“…Since w slow , 1, we can approximate w fast M w,fast to M w,fast , and Table 2 lists the aggregation number M w,fast /M w of the fast- 19 (see above). This indicates that the major small aggregate of poly(NaAMPS/C 6 MA) takes a more compact conformation than the NaAMPS homopolymer does in aqueous NaCl presumably because of the hydrophobic interaction among C 6 MA monomer units within the aggregate.…”
Section: Resultsmentioning
confidence: 99%
“…However, eqn (1) may not be applicable at high c IL because, in reality, polyelectrolyte chains shrink and eventually reach the initial polyelectrolyte chain size at high c IL when the charge is completely screened. [28][29][30] Dobrynin and coworkers 31,32 have recently reported that the finite chain dimension of polyelectrolytes in the absence of electrostatics depends on chains persistent length and the second virial coefficient.…”
Section: Introductionmentioning
confidence: 99%